Management Effectiveness of Sheikh Baden National Park: Testing the Scope of Cultural Integrity - AHMAD, Waqar; ULLAH, Asad; KHAN, Younas; ARIF, Muhammad; AHMAD, Usama (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).14, 2021)
A cross sectional-based research was conducted with the sole aim to assess the management effectiveness of Sheikh Baden National Park [SBNP] District Dera Ismail Khan Khyber Pakhtunkhwa, Pakistan with respect to cultural integrity. A sample size of 389 respondents were selected through simple random sampling to determine respondents attitude towards cultural integrity (independent variable) and management effectiveness of SBNP (dependent variable) through Likert scale as measurement tool. Further, descriptive (univaraite analysis) and inferential statistics (bivariate analysis) were carried out. With regards to bivariate results found that, an association of management effectiveness of SBNP was highly significant with historical events (p=0.004), introducing local culture to visitors (p=0.000), access to culturally rich areas (p=0.000), display of cultural events (p=0.000), handicrafts and food items production and promotion (p=0.000), alternate livelihood for disturbed communities (p=0.000) and trained wildlife staff (p=0.000). Improvements in promotion of SBNP and its related ecological, cultural and historical importance at mass scale by using both conventional and modern communication channels including mass media, print media, internet and social media etc. were major recommendations in light of the study.